Whistleblowers or Witnesses - Lovell, Alan (Henry Stewart Talks, 2011)
The language of whistleblowing, Loyalty, Virtue or vice?, When is a whistleblowing act performed?, Why whistleblow?, Costs of whistleblowing, When might a whistleblowing act be justified?, The Public Interest Disclosure Act (1998), Whistleblowing: a positive or negative force within society?, Understanding what 'gives' when a potential whistleblowing scenario either dissolves or explodes, Floating responsibility, Reflections